Tissue-specific glucose partitioning and fat content in prediabetes and type 2 diabetes: whole-body PET/MRI during hyperinsulinemia. Issue 6 (10th May 2021) - Eriksson, Jan W; Visvanathar, Robin; Kullberg, Joel; Strand, Robin; Skrtic, Stanko; Ekström, Simon; Lubberink, Mark; Lundqvist, Martin H; Katsogiannos, Petros; Pereira, Maria J; Ahlström, Håkan
Abstract : Objective: To obtain direct quantifications of glucose turnover, volumes and fat content of several tissues in the development of type 2 diabetes (T2D) using a novel integrated approach for whole-body imaging. Design and methods: Hyperinsulinemic–euglycemic clamps and simultaneous whole-body integrated [ 18 F]FDG-PET/MRI with automated analyses were performed in control ( n  = 12), prediabetes ( n  = 16) and T2D ( n  = 13) subjects matched for age, sex and BMI. Results: Whole-body glucose uptake (Rd) was reduced by approximately 25% in T2D vs control subjects, and partitioning to brain was increased from 3.8% of total Rd in controls to 7.1% in T2D. In liver, subcutaneous AT, thigh muscle, total tissue glucose metabolic rates (MRglu ) and their % of total Rd were reduced in T2D compared to control subjects. The prediabetes group had intermediate findings. Total MRglu in heart, visceral AT, gluteus and calf muscle was similar across groups. Whole-body insulin sensitivity assessed as glucose infusion rate correlated with liver MRglu but inversely with brain MRglu . Liver fat content correlated with MRglu in brain but inversely with MRglu in other tissues. Calf muscle fat was inversely associated with MRglu only in the same muscle group. Conclusions: This integrated imaging approach provides detailed quantification of tissue-specific glucose metabolism. During T2D development, insulin-stimulated glucose disposal is impaired and increasingly shifted away from muscle, liver and fat toward the brain. Altered glucose handling in the brain and liver fat accumulation may aggravate insulin resistance in several organs.